Portugal in a European Context
XXII, 331 p. 5 illus., 3 illus. in color.
Keywords: Although Portugal was one of the first European states with stable borders, the process of the making of a Portuguese fiscal state still remains to be studied in detail. This volume brings together studies on the development of the Portuguese fiscal state within a comparative perspective in relation to other kingdoms across Europe, such as Castile and Aragon, England, Tuscany, the Papal States, Holland and France, in order to bring Portugal into the broader and comparative international debate about the development of the fiscal state. As a very distinctive case, Portugal remains understudied and underrepresented in the broader literature on the development of fiscal states. There are relatively few studies on the building of a fiscal state in Portugal that are accessible to an international audience. This book will make a fundamental contribution to this field, which is still full of untapped potential. It will combine the latest theory and comparative context with a detailed reconstruction of Portuguese state finance, taking a longer chronological frame that follows its development from the medieval through to the early modern period. It will also make the latest research from Portuguese scholars available to a wider, international audience, and will be of particular interest to researchers and students of financial and economic history. Rodrigo da Costa Dominguez is currently a Junior Research Associate and Director of the Interdisciplinary Center of Social Sciences (CICS.NOVA) at the University of Minho, in Braga, Portugal. His expertise relies on the Fiscal History of Portugal in the long-run (14th-20th century). He is also a member of international economic, fiscal, and social history associations in Portugal, Spain, Brazil, Latin America and United States, being a member of the Arca Comunis Group (a network of research projects on the History of Hispanic Finance and Taxation, 13th-18th centuries) and also President-elect of the Economic and Business History Society (EBHS – USA) for the mandates 2020-2021 and 2022-2023. Amélia Aguiar Andrade is a Full Professor of Medieval History at the Faculty of Social and Human Sciences, New University of Lisbon (NOVA FCSH), Portugal. She has held numerous scientific and university positions, in Portugal and abroad, being recently accepted in the College of Expert Reviewers of the European Science Foundation (ESF). From 2009 to 2012, she was Vice-Dean of the Faculty of Social and Human Sciences, for which she received a public praise and headed the Institute of Medieval Studies of the same faculty between 2011 and 2016. She is also a member of the Scientific Council of NOVA FCSH, including the vice-presidency from 2006 to 2008 and 2021-22. Among her international curriculum, it's to highlight that she chaired Scientific Committee of the European Association for Urban History (2012-2014) which he served from 2008-2016. She is also the PI of ROSSIO - Infrastructure for Social Sciences, Arts and Humanities and national representative in the European infrastructure DARIAH.